Análisis de la Sostenibilidad de la Política Fiscal y el Efecto del Gasto Público sobre la Economía. 1994-2006 - Álvarez Betancourt, Silvia (2006)
Ecuador has a long history of fiscal deficits. This analysis asks whether the magnitude of these deficits has involved a violation of Ecuador”s intertemporal budget constraint, 1t is to say whether or not the Ecuadorian fiscal policy is sustainable. It is not only important to evaluate the sustainability of the fiscal policy, 1t is also important to know if the public expenditure helps to stabilize the economy. Á cointegration analysis with three variables (GDP, public expenditure and fiscal earnings) was used in order to verify the sustainability and the stabilizer role of the fiscal policy. The conclusion was that Ecuador”s fiscal policy is weakly sustainable, but it has achieved to stabilize the economy.